2018
DOI: 10.1007/s00894-018-3653-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effect of oxygen-containing functional groups on the water-holding capacity of lignite

Abstract: Graphene oxide with different degrees of oxidation was prepared and selected as a model compound of lignite to study quantitatively, using both experiment and theoretical calculation methods, the effect on water-holding capacity of oxygen-containing functional groups. The experimental results showed that graphite can be oxidized, and forms epoxy groups most easily, followed by hydroxyl and carboxyl groups. The prepared graphene oxide forms a membrane-state as a single layer structure, with an irregular surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Molecular simulation of the adsorption of some water molecules into porous carbon materials can be found in literature. Feng et al used carbon nanotubes, graphene oxide, and small molecules with different OFGs as lignite monomers to investigate the interaction between OFG and water ( n H 2 O@OFG) and found that the interaction energy between water and carboxyl molecules ( n H 2 O@carboxyl) was the largest, followed by the interaction with phenolic hydroxyl, carbonyl, and benzene, which was similar to the results obtained by Wu et al (interaction of 1H 2 O@OFG carboxyl > phenolic hydroxyl > carbonyl > alcoholic hydroxyl > ether). Wu et al also accurately demonstrated the hydrogen bonds (HB), van der Waals interactions, and steric repulsion by reduced density gradient isosurface.…”
Section: Introductionsupporting
confidence: 65%
“…Molecular simulation of the adsorption of some water molecules into porous carbon materials can be found in literature. Feng et al used carbon nanotubes, graphene oxide, and small molecules with different OFGs as lignite monomers to investigate the interaction between OFG and water ( n H 2 O@OFG) and found that the interaction energy between water and carboxyl molecules ( n H 2 O@carboxyl) was the largest, followed by the interaction with phenolic hydroxyl, carbonyl, and benzene, which was similar to the results obtained by Wu et al (interaction of 1H 2 O@OFG carboxyl > phenolic hydroxyl > carbonyl > alcoholic hydroxyl > ether). Wu et al also accurately demonstrated the hydrogen bonds (HB), van der Waals interactions, and steric repulsion by reduced density gradient isosurface.…”
Section: Introductionsupporting
confidence: 65%
“…The SDF has a certain degree of water absorption capacity, which can increase the WHC. The increase in SDF content (6.91–20.82% versus 2.61–5.86%) caused an increase in the WHC of bran, which may be due to the exposure of hydroxyl and carboxyl groups to water molecules as a result of the instantaneous shear stress from SE 31 . SE bran had significantly higher SC than native bran did ( α = 0.01) (Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…The increase in SDF content (6.91-20.82% versus 2.61-5.86%) caused an increase in the WHC of bran, which may be due to the exposure of hydroxyl and carboxyl groups to water molecules as a result of the instantaneous shear stress from SE. 31 SE bran had significantly higher SC than native bran did (⊍ = 0.01) (Table 2). The observed results are consistent with the finding of a recent study, 24 which may be due to the increase in the number of short chains and surface area of SDF due to SE.…”
Section: Effect Of Se Pressure On Functional Properties Of Wheat Branmentioning
confidence: 94%
“…The adsorption of water is associated with not only the pore characteristics of coal but also the number of oxygen-containing functional groups in coal. 78,79 As shown in Figure 12F, the low-rank coal sample YZG2 has a greater equilibrium moisture content, which is mainly due to the existence of a large amount of oxygen-containing functional groups in the low-rank coal. Conversely, the medium-and high-rank coals have few oxygen-containing functional groups, so their water-holding capacity is mainly influenced by the pore structure of the coal.…”
Section: Relationship Between the Fractal Dimension And Adsorption mentioning
confidence: 99%